Pembuatan Sistem Aplikasi Electronic Voting (E-Voting) Berbasis Web dengan Pendekatan Metode Waterfall - Nurdiansyah, Rendy; Suryawan, Sayekti Harist; Rahim, Abdul (Jurnal Informatika Terpadu, 2024)
Electronic voting (e-voting) uses electronic devices to simplify the voting process, enabling quick selection, vote tabulation, and real-time access to information. Traditional voting methods have various drawbacks, such as high costs, risk of human error, lengthy counting processes, and vulnerability to fraud. Universitas Muhammadiyah Kalimantan Timur (UMKT) also faces similar challenges in its internal organizational elections. The e-voting system is designed to overcome these obstacles by enhancing efficiency and transparency and reducing errors through an accurate audit trail. This study aims to develop a web-based e-voting application that can address the problems associated with traditional voting methods. The application is developed using Python, the programming language of the Django framework, and MySQL for database management. The development method employed is the Waterfall model, which provides a clear structure and project schedule. The research results indicate that the black box testing of this application was successful. Furthermore, testing using the Technology Acceptance Model (TAM) shows that the Web-Based E-voting Application System has an average percentage score of 91%, indicating that most respondents agree or strongly agree with using this system. Thus, this e-voting system is expected to increase voter participation, reduce operational costs, and ensure that every vote is counted accurately while addressing the various issues faced by traditional voting methods.